Estado punitivista: o encarceramento da população negra no Brasil - Silva, Katiana Ventura da (2024)
This Master's Dissertation consists of an analysis of the Brazilian penal system, seeking to highlight its characteristics as a State apparatus for social control and oppression of the subordinated layers of society, reproducing social inequality, inherent to the capitalist order. The study privileges the relationship between the social issue and the criminal issue, identifying the mechanisms through which Justice and Public Security System operators contribute to the alleged fight against crime, from a punitive perspective, in order to favor the interests of dominant groups to the detriment of population segments considered deviant or transgressive of the established order. In other words, a model of “justice” that opposes the group of “punishable” to the group of “non-punishable”. From this perspective, it was possible to collect data that demonstrate the selectivity of the penal system, which causes segregationist, criminalizing and punitive anger to fall on segments of the black population. The choice of the methodological path was inspired by marxist materialist dialectics, which justifies the search for theoretical support in the literature of critical criminology in an open confrontation with positivist criminology, alongside the effort to understand the functions of the penal system as part of the mechanisms of perpetuation of the current capitalist order, highlighting the decisive and persistent character of racism and slave labor in the social, political, economic and cultural constitution of Brazilian society. The research methodological procedures included bibliographic and documentary research; the analysis of the legislative collection of the area in question; the approach to the main historical milestones of policies aimed at public security; the organization of an inventory of court sentences and police actions, highlighting criminal selectivity; and the incursion, albeit brief, into the controversy over central aspects of Criminal Law, such as the notions of heinous crime, drug legislation, the presumption of innocence, (un)founded suspicion and the principle of insignificance, among others. With the results of the research, once again, any illusions regarding the alleged racial democracy, converted into a myth, are dispelled. The importance of fighting strategies on social, economic, cultural and legal levels is highlighted, in the uncompromising defense of human rights and social justice